Doença de chagas e gravidez - Antoun, Raif (2000)
Chagas disease is endemic in Latin America, with prevalence in pregnant women between 20 and 58%. The risk of congenital transmission ranges from 1 to 10%. The undetermined form corresponds to 70% of the chagasic patients, has a good prognosis, with similar mortality rates to healthy individuals of the same age group. Pregnancy promotes changes in the cardiovascular and respiratory system, hormonal and metabolic as likely factors of decompensation and higher incidence of cardiac arrhythmia. The study was developed at the Cardiopathy and Pregnancy Outpatient Clinic in the High Risk Pregnancy sector of the Department of Gynecology and Obstetrics and at the Obstetrics and Cardiology Discipline of the Hospital de Clínicas of the School of Medicine of the Federal University of Uberlândia. Fifty-four pregnant women with Chagas disease and 50 normal pregnant women were studied. The chagasic group was subdivided into a group without apparent (undetermined) heart disease consisting of 34 pregnant women and the group with chronic chagasic heart disease with cardiomyopathy and / or arrhythmia composed of 20 pregnant women. Gestational age, number of pregnancies, number of prenatal consultations, type of delivery, type of anesthesia, apgar score, newborn weight, association between newborn weight and functional type, as well as gestational age, were evaluated. type of childbirth, apgar, in chagas disease without apparent heart disease and with heart disease; The electrocardiographic and echocardiographic alterations of the chagasic groups and complications during pregnancy were also evaluated. Chi-square statistical analysis, destudent t test, and variance analysis were used to statistically observe the obtained data. What was observed were pregnancies with a low number of complications, even in the presence of significant changes in rhythm and conduction. The greater number of prenatal consultations in the group with heart disease was determinant in the lower number of maternal and fetal complications. Regarding prematurity, abortion, apgar weight and weight, these do not differ significantly between the chagasic group and the control group; however, the incidence of Apgar in pregnant women in the control group was smaller. It is concluded that, in the chronic chagasic group, the number of complications was small in most of the studied variables, but deserves special medical attention due to the potential risks associated with the disease. pregnancy.